Designing Number Pattern Questions to Assess Students with Kinesthetic Learning Styles' in Mathematical Thinking - Susanti, Ely; Delfi, Iftina; Hapizah, Hapizah; Indaryanti, Indaryanti; Isrok'atun, Isrok'atun; Simarmata, Ruth Helen (SJME (Supremum Journal of Mathematics Education), 2024)
The aim of the research is to describe the results of designing number pattern questions used to measure the mathematical thinking abilities of students with a kinesthetic learning style. The research subjects consisted of 5 class VIII students with a kinesthetic learning style. The type of research is design research with 5 stages, namely: Preliminary Design, Focus Group Discussion (FGD), Trial, Interview, and Retrospective Analysis. The data collection techniques are learning style questionnaires, tests and interviews. The data analysis used in the research is qualitative. Based on the results of the FGD, number pattern questions can be used to measure mathematical thinking abilities, because each question leads students to bring up specializing, generalizing, conjecturing and convincing aspects. Based on the test results, it is known that students can write specializing, generalizing, conjecturing, and convincing forms. Specializing is seen when students write the form of adding numbers for each term. Generalizing is seen when students find patterns by listing them one by one or using tables, conjecturing when they find the general formula, and convincing is seen when they find other ways to prove the answer. Based on the results of the interview, students' answers were obtained through the activity of managing and simulating questions using body parts.